A sustainable review of the Middle Pleistocene benchmark sites including the Ailuropoda–Stegodon faunal complex: The Proboscidean point of view. (19th September 2016) - Zeitoun, Valery; Chinnawut, Winayalai; Debruyne, Régis; Frère, Stéphane; Auetrakulvit, Prasit
Abstract: The different ecologies, times of extinction and 'last stand' of both Elephas and Stegodon in South-east Asia cover almost two million years. In the Middle Pleistocene, both taxa belong to the complex Ailuropoda–Stegodon . This regional complex is considered to have a chronological significance, and further palaeoecological, palaeobiogeographical or biochronological studies use this assemblage as a benchmark. Nevertheless, such studies do not provide sufficient information regarding site formation and duration to be consistent enough to do so at an appropriate resolution (MIS timescale). Focussing attention on the occurrence of Proboscideans, a critical review of the robustness of the geological, taphonomical and chronological data of Middle Pleistocene faunal assemblages suggests the necessity to undertake a deep reappraisal of this "biochronological benchmark". Recommendations were provided in the 1980s not to use mixtures of faunal assemblages, and progress in geochronology for two decades is available. Nevertheless, a review of Proboscideans suggests the necessity of a severe revision, leading to scepticism concerning the use of the Ailuropoda–Stegodon complex as an ecological marker. Extended to other taxa, this review casts serious doubts on former and current paleoecological modellings and studies.